ANALYSIS OF THE IMPLEMENTATION OF THE TRADITIONAL MARKET REVITALIZATION PROGRAM IN JEMBER REGENCY BASED ON THE THEORY OF GEORGE EDWARDS III - Afa Ayun Avinas; Ria Angin (POLITICO, 2020)
The purpose of this research  is to describe the implementation of a traditional market revitalization program in Jember Regency. The research method uses a qualitative descriptive approach. The object of research is the Head of Infrastructure Facilities, staff working at the Ministry of Industry and Trade, and Assistant Treasurer as manager of the Mangli Market in Jember Regency. Data collection through interviews, observation, and documentation. Based on the research finding,  George Edward III's theory is not fully able to describe the phenomenon in the field. George Edward III only explained that the success of the policy implementation process was determined by 4 variables namely communication, resources, disposition and bureaucratic structure. The phenomenon in the field shows that the variable resources consist of budgetary resources, human resources and infrastructure resources. These three resources are not discussed in George Edward III's theory. Therefore  the theory of George Edward III had limitations as an analytical tool.